The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1111/j.1748-7692.1995.tb00273.x
|View full text |Cite
|
Sign up to set email alerts
|

INTRASPECIFIC GENETIC DIFFERENTIATION IN CALIFORNIA SEA LIONS (ZALOPHUS CALIFORNIANUS) FROM SOUTHERN CALIFORNIA AND THE GULF OF CALIFORNIA

Abstract: Intraspecific patterns of mitochondrial DNA sequence variation were determined among California sea lions (Zalophus califomianus californianus) from three colonies along the Pacific coast of southern and Baja California and one colony in the Gulf of California. We found no variation in 368 base pairs (bp) of cytochrome b sequence among 40 sea lions from these localities, but analysis of 360 base pairs of control region revealed eleven genotypes. The four genotypes found in the Gulf of California population wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 34 publications
2
43
1
1
Order By: Relevance
“…There are two exceptions: one OTU each for Z. californians and A. townsendi. Because Maldonado et al (1995) found no variation in 368 bp of the same cytochrome b region of 40 Z. californianus individuals, the combination of the regions from unknown individuals was not considered problematic in this case. The A. townsendi OTU (ATO45) resulted from the control region sequence of ATO4 and cytochrome b sequence of ATO5.…”
Section: Phylogeny Of the Otariidaementioning
confidence: 89%
See 1 more Smart Citation
“…There are two exceptions: one OTU each for Z. californians and A. townsendi. Because Maldonado et al (1995) found no variation in 368 bp of the same cytochrome b region of 40 Z. californianus individuals, the combination of the regions from unknown individuals was not considered problematic in this case. The A. townsendi OTU (ATO45) resulted from the control region sequence of ATO4 and cytochrome b sequence of ATO5.…”
Section: Phylogeny Of the Otariidaementioning
confidence: 89%
“…a Sequenced as part of this study; b Sequenced as part of Wynen et al, 2000; c Genbank (Lento et al, 1997); d Lento, 1995; e Goldsworthy et al, 2000; f Sequenced as part of this study by Rus Hoelzel; g Genbank (Maldonado et al, 1995); h Genbank (Masuda and Yoshida, 1994); i Genbank (Arnason et al, 1995); j Genbank (Arnason and Johnsson, 1992). Genbank accession numbers are listed where relevant; * Overall values presented for ingroup taxa only.…”
Section: Laboratory Analysismentioning
confidence: 98%
“…Universal primers Thr-L15910 and DL-H16498 (Kocher et al 1989) were used in PCR reactions to amplify a 601 bp fragment including the 5' domain and the conserved blocks F and E of the control region (Douzery and Randy 1997), following protocols described by Gonza´lez (1997). In addition, a 486 bp fragment of cytochrome b gene was amplified for 44 representative individuals from all localities using primers L14724 and H15149, as described in Maldonado et al (1995). DNA extractions and PCR reactions were performed at the genetic facilities at IIBCE (Uruguay) and at Departamento de Zootecnia, FCAV/ UNESP (Brazil).…”
Section: Extraction Amplification and Mtdna Sequencingmentioning
confidence: 99%
“…1). These include marine mammals, invertebrates, and approximately 19 species of fishes (Miller and Lea 1972;Present 1987;Maldonado et al 1995;Medina and Walsh 2000;Thomson et al 2000; Table 1). While the concept of disjunction refers to intraspecific geographic separation, in two cases of Pacific Ocean/Gulf of California fishes, species rankings were given to each group.…”
mentioning
confidence: 99%